Symbols, Self-Interest and Labour Policy Attitudes: Evidence from Saskatchewan - Berdahl, Loleen; White, Stephen; McGrane, David; Atkinson, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2014)
Unions in many Canadian jurisdictions are facing policy changes that limit (or attempt to limit) their practices. Despite growing pressure on unions as governments restructure labour policies, there is scant research examining public attitudes towards either unions or labour policies. To what extent does the general public support or oppose these changes to labour policy? What factors drive public opinion about labour policy changes?This paper uses data from a telephone survey administered after the 2011 Saskatchewan provincial election to explore public attitudes towards labour policy change; specifically, we explore public opinion regarding Saskatchewan essential services legislation and accompanying changes to labour standards. We are particularly interested in the role that symbolic political factors (attitudes towards unions, NDP partisanship), as opposed to self-interest (union membership), play in structuring public opinion when it comes to labour policy. We find that union membership has no discernible impact on attitudes toward the essential services law; what matters much more is one’s attitude toward unions in general, as well as NDP partisanship. However, union membership does influence attitudes towards labour standards, as do attitudes towards unions and NDP partisanship.Taken together, the results tell us that labour policy attitudes are indeed driven by both self-interest and symbolic political factors. Further, while self-interest does help to explain attitudes towards labour policy, not all union members consider essential services legislation as a direct threat to themselves. The strategic implication for public sector unions is that they cannot necessarily rely on private sector workers and union members to be sympathetic to legislation that affects public sector workplaces. For the Canadian labour movement as a whole, this finding points towards a divergence in the interests of its private sector members and public sector members, and clear limits to worker solidarity.